2022
DOI: 10.1038/s41431-022-01226-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing with gene panel-based analysis for rare inherited conditions in a publicly funded healthcare system: implications for future testing

Abstract: NHS genetics centres in Scotland sought to investigate the Genomics England 100,000 Genomes Project diagnostic utility to evaluate genome sequencing for in rare, inherited conditions. Four regional services recruited 999 individuals from 394 families in 200 rare phenotype categories, with negative historic genetic testing. Genome sequencing was performed at Edinburgh Genomics, and phenotype and sequence data were transferred to Genomics England for variant calling, gene-based filtering and variant prioritisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…This study is a step towards shedding light on the factors that render genome sequencing non-diagnostic through deep analysis of real-world data from a large Mendelian program with excellent sampling representation from one of the largest countries in the Middle East. Contrary to the common belief that the missing diagnostic yield of exome is mostly related to technical limitations 36 , 37 , we have previously shown using an unbiased positional mapping approach that at least in the setting of autosomal recessive phenotypes in consanguineous populations, more than 90% of causal variants should in theory be detectable by exome sequencing 5 . Indeed, we and others have shown that reanalysis of “negative” exome sequencing uncovers causal variants that were missed at the interpretation rather than capture stages 38 42 .…”
Section: Discussioncontrasting
confidence: 66%
“…This study is a step towards shedding light on the factors that render genome sequencing non-diagnostic through deep analysis of real-world data from a large Mendelian program with excellent sampling representation from one of the largest countries in the Middle East. Contrary to the common belief that the missing diagnostic yield of exome is mostly related to technical limitations 36 , 37 , we have previously shown using an unbiased positional mapping approach that at least in the setting of autosomal recessive phenotypes in consanguineous populations, more than 90% of causal variants should in theory be detectable by exome sequencing 5 . Indeed, we and others have shown that reanalysis of “negative” exome sequencing uncovers causal variants that were missed at the interpretation rather than capture stages 38 42 .…”
Section: Discussioncontrasting
confidence: 66%
“…7,8 Diagnostic GS yield from large, rare disease cohort studies is 20% to 40% depending on disease subtypes. [9][10][11][12][13] Although the actual magnitude is still debatable, the diagnostic sensitivity of GS surpasses that of other genetic testing options, including ES. 11,12,[14][15][16][17][18] The clinical utility of rapid GS has been best demonstrated for critically ill pediatric patients, affecting health care management and resulting in better outcomes and significant health care cost savings.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic GS yield from large, rare disease cohort studies is 20% to 40% depending on disease subtypes . Although the actual magnitude is still debatable, the diagnostic sensitivity of GS surpasses that of other genetic testing options, including ES .…”
Section: Introductionmentioning
confidence: 99%
“…Short stature associated with PRMT7 variants may respond to growth hormone [5]. Genome sequencing is the available first line genome test in the UK National Health Service; but Hocking et al provide further evidence that the increased cost does not perhaps result in an increased diagnostic yield [6]. Using genomic testing in post-natal settings is well established, but its use prenatally is controversial.…”
mentioning
confidence: 99%